2009
DOI: 10.1890/08-0964.1
|View full text |Cite
|
Sign up to set email alerts
|

Declines in predatory fish promote bloom‐forming macroalgae

Abstract: In the Baltic Sea, increased dominance of ephemeral and bloom-forming algae is presently attributed to increased nutrient loads. Simultaneously, coastal predatory fish are in strong decline. Using field data from nine areas covering a 700-km coastline, we examined whether formation of macroalgal blooms could be linked to the composition of the fish community. We then tested whether predator or nutrient availability could explain the field patterns in two small-scale field experiments, by comparing joint effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
156
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(172 citation statements)
references
References 48 publications
14
156
0
2
Order By: Relevance
“…In some cases algal biomass appears to be as, or more, sensitive to topdown pressure within the food web as algae are to resource availability (Heffernan et al 2010, Perga et al 2010. The importance of top-down effects on processes that have historically been considered symptoms of eutrophication has recently been examined in experimental research (Eriksson et al 2009, Baden et al 2010) and time series analysis (Baden et al 2012). Our study took advantage of an ecosystem with the unique, long-term data on multiple trophic levels to explore a particular scenario of resource availability versus fish: the potential trophic cascade between anadromous fish and phytoplankton.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases algal biomass appears to be as, or more, sensitive to topdown pressure within the food web as algae are to resource availability (Heffernan et al 2010, Perga et al 2010. The importance of top-down effects on processes that have historically been considered symptoms of eutrophication has recently been examined in experimental research (Eriksson et al 2009, Baden et al 2010) and time series analysis (Baden et al 2012). Our study took advantage of an ecosystem with the unique, long-term data on multiple trophic levels to explore a particular scenario of resource availability versus fish: the potential trophic cascade between anadromous fish and phytoplankton.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between jellyfish and chlorophyll a concentration in the Yellow Sea suggest a cascading effect resulting from the jellyfish grazing on zooplankton that in turn reduce the grazing of zooplankton on phytoplankton (Dong et al 2012). This has been observed in the Baltic Sea where research revealed that declines in predatory fish promoted blooms of macroalgae with cascading effects down the food web (Eriksson et al 2009). Additionally, macroalgal blooms could strengthen hypoxic conditions which in turn further degrade the coastal ecosystems (Smetacek and Zingone 2013).…”
Section: Synergistic Effects and Cascading Shiftsmentioning
confidence: 92%
“…Accordingly, field studies support a positive relationship between primary production and trophic cascades in some systems (e.g., Sinclair et al 2000;Elmhagen and Rushton 2007;Moksnes et al 2008;Eriksson et al 2009;Sieben et al 2011), whereas a recent set of meta-analyses suggests that, in general, it is the traits of consumer species, and not productivity, that determine the prevalence of trophic cascades in predator removal experiments (Borer et al 2005(Borer et al , 2006. However, models that incorporate short-term population dynamics and allow for dispersal suggest that the an alternating positive relationship between trophic levels and primary productivity should also appear in environments where consumers immigrate and emigrate actively between patches depending on resource availability (Wootton and Power 1993;Oksanen et al 1995;Nisbet et al 1997).…”
Section: Introductionmentioning
confidence: 95%